Method for testing silicon nitride thin films

CN122962374APending Publication Date: 2026-10-23CHUZHOU JIETAI NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611022446.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-09
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

然而,常规的测试方法普遍局限于膜厚、折射率、少子寿命等基础参数,且存在工况模拟不足的问题,未能有效关联光伏电池在高温高湿、工作偏压、长期湿热老化等实际服役环境下的可靠性表现,导致测试结果不能准确反映膜层质量及光伏电池的整体可靠性

Benefits of technology

[0014]上述氮化硅薄膜测试方法,通过高压加速湿热老化处理能够有效模拟待测样品,如光伏电池在高温、高湿、高气压等实际服役环境下的老化过程,使膜层及界面潜在缺陷在加速应力下充分暴露,避免了常规测试因工况脱离实际而导致的评价失真。同时,通过分别获取并比对老化处理前后的电性能参数、钝化参数及致密性参数,实现了对氮化硅薄膜多个维度的综合量化评价,有效避免了单一指标测试导致的信息不全或误判。因此,上述氮化硅薄膜测试方法的准确性大大提升,其测试结果能够真实反映膜层质量及光伏电池的整体可靠性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122962374A_ABST
    Figure CN122962374A_ABST
Patent Text Reader

Abstract

The present application relates to a kind of silicon nitride film test methods, through high pressure accelerated humid heat aging treatment can effectively simulate the aging process of the sample to be measured, such as photovoltaic cell in high temperature, high humidity, high pressure and other practical service environment, make film layer and interface potential defect fully exposed under accelerated stress, avoid the evaluation distortion caused by the conventional test due to the working condition deviating from reality.At the same time, by respectively acquiring and comparing the electrical performance parameters, passivation parameters and density parameters before and after aging treatment, the comprehensive quantitative evaluation of silicon nitride film in multiple dimensions is realized, which effectively avoids the incomplete information or misjudgment caused by single index test.Therefore, the accuracy of the above-mentioned silicon nitride film test method is greatly improved, and the test result can truly reflect the quality of film layer and the overall reliability of photovoltaic cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of photovoltaic cell technology, and in particular to a testing method for silicon nitride thin films. Background Technology

[0002] In crystalline silicon solar cells, silicon nitride thin films serve as the core functional layer, playing multiple crucial roles such as surface passivation, anti-reflection, resistance to moisture erosion, and hindering metal ion migration. Their quality directly determines the cell's conversion efficiency, aging stability, and service life. Especially for N-type TOPCon cells, the silicon nitride thin film needs to work in conjunction with the tunneling oxide layer and polycrystalline silicon layer to construct a high-quality passivation contact structure. This places even stricter requirements on the film's density, uniformity, and interface stability, necessitating targeted testing of various silicon nitride film properties. However, conventional testing methods are generally limited to basic parameters such as film thickness, refractive index, and minority carrier lifetime, and suffer from insufficient simulation of operating conditions. They fail to effectively correlate the reliability performance of photovoltaic cells under actual service environments such as high temperature and humidity, operating bias, and long-term damp heat aging, resulting in test results that cannot accurately reflect the film quality and the overall reliability of the photovoltaic cell. Summary of the Invention

[0003] Therefore, it is necessary to provide a silicon nitride thin film testing method that can improve the accuracy of test results to address the above problems.

[0004] A method for testing silicon nitride thin films, comprising the following steps: Initial performance tests are performed on the sample to be tested to obtain the initial electrical performance parameters, initial passivation parameters, and initial compactness parameters of the sample to be tested. The sample to be tested was subjected to high-pressure accelerated damp heat aging treatment; The test sample after aging treatment is subjected to a second performance test to obtain the aging electrical performance parameters, aging passivation parameters and aging densification parameters of the test sample. The decay index is obtained by comparing the aging electrical performance parameters, the aging passivation parameters, and the aging densification parameters with the initial electrical performance parameters, the initial passivation parameters, and the initial densification parameters, respectively. The sample is deemed qualified when the decay index is lower than the corresponding threshold.

[0005] In one embodiment, the sample to be tested is a TOPCon battery, the surface of which is coated with a silicon nitride film.

[0006] In one embodiment, before performing initial performance testing on the sample to be tested, the method further includes the following steps: detecting the film thickness, refractive index, and luminescence uniformity of the sample, and selecting samples with film thickness deviation ≤ ±2nm, refractive index between 1.9 and 2.1, and qualified luminescence uniformity as the sample to be tested.

[0007] In one embodiment, before performing another performance test on the aged sample, the method further includes the step of: performing microscopic morphology analysis on the sample by scanning electron microscopy-energy dispersive spectroscopy, and determining the sample that fails the morphology analysis as unqualified.

[0008] In one embodiment, the step of subjecting the test sample to high-pressure accelerated damp heat aging treatment includes: setting the test parameters to a temperature of 130°C, a relative humidity of 85%RH, and a pressure of 2230kPa; then placing the test sample in a test chamber for continuous testing for 96 hours, and applying a bias voltage of 0.6 to 0.8 times the open circuit voltage; and then taking the test sample out and placing it in an environment with a temperature of 25°C and a relative humidity of 60%RH for 4 hours to recover.

[0009] In one embodiment, the initial electrical performance parameters include initial series resistance, initial parallel resistance, initial conversion efficiency, and initial leakage current; the initial passivation parameters include initial minority carrier lifetime; and the initial compaction parameters include initial film thickness. The aging electrical performance parameters include series resistance after aging, parallel resistance after aging, conversion efficiency after aging, and leakage current after aging; the aging passivation parameters include minority carrier lifetime after aging; and the aging compaction parameters include film thickness after aging. The degradation index includes film thickness loss rate, minority carrier lifetime decay rate, series resistance increase, parallel resistance decay rate, conversion efficiency decay rate, and leakage current increase. The sample to be tested is deemed qualified when the following conditions are met: film thickness loss rate ≤3%, minority carrier lifetime decay rate ≤25%, series resistance increase ≤15%, parallel resistance decay rate ≤20%, conversion efficiency decay rate ≤5%, and leakage current increase ≤200%.

[0010] In one embodiment, when the test sample is subjected to a second performance test, an EL / PL imaging device is used to detect the structural defects of the test sample after aging treatment, and the area ratio of the area with structural defects is obtained. The test sample can be judged as qualified only if the area ratio is ≤1%.

[0011] In one embodiment, the step of performing a second performance test on the sample to be tested to obtain the aged film thickness includes: Prepare a 1% dilute hydrofluoric acid solution, immerse the sample to be tested in the solution for 30 seconds, remove it, rinse it with deionized water and then dry it with nitrogen gas; observe the surface morphology of the film layer of the sample to be tested using an optical microscope to conduct a preliminary test of its density; measure the thickness of the sample to be tested if the preliminary test of density is qualified.

[0012] In one embodiment, the step of performing a second performance test on the test sample to obtain the leakage current after aging includes: placing the aged test sample in a humid and hot environment with a temperature of 85°C and a relative humidity of 85%RH and applying a DC bias voltage of 10V; continuously testing for 24 hours and obtaining the leakage current after aging.

[0013] In one embodiment, after the sample to be tested is tested again, a high-temperature thermal stability test is also included: the aged sample to be tested is placed in a vacuum oven at 200°C for 1 hour and then naturally cooled to room temperature; the minority carrier lifetime and conversion efficiency after high-temperature treatment are retested, and the high-temperature performance degradation rate is obtained. Only when the high-temperature performance degradation rate is ≤2% can the sample to be tested be determined as qualified.

[0014] The aforementioned silicon nitride thin film testing method effectively simulates the aging process of the sample under test, such as a photovoltaic cell, in actual service environments with high temperature, high humidity, and high pressure through high-pressure accelerated damp-heat aging treatment. This fully exposes potential defects in the film layer and interface under accelerated stress, avoiding the evaluation distortion caused by conventional testing due to unrealistic operating conditions. Simultaneously, by acquiring and comparing the electrical performance parameters, passivation parameters, and density parameters before and after aging treatment, a comprehensive quantitative evaluation of the silicon nitride thin film across multiple dimensions is achieved, effectively avoiding incomplete information or misjudgments caused by testing a single indicator. Therefore, the accuracy of the aforementioned silicon nitride thin film testing method is greatly improved, and its test results can truly reflect the film quality and the overall reliability of the photovoltaic cell. Attached Figure Description

[0015] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0016] Figure 1 This is a schematic flowchart of a silicon nitride thin film testing method in one embodiment of the present invention. Detailed Implementation

[0017] To make the above-mentioned objects, features, and advantages of the present invention more apparent and understandable, specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings. Many specific details are set forth in the following description to provide a thorough understanding of the present invention. However, the present invention can be practiced in many other ways different from those described herein, and those skilled in the art can make similar modifications without departing from the spirit of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0018] In the description of this invention, it should be understood that the terms "center," "longitudinal," "lateral," "length," "width," "thickness," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," "outer," "clockwise," "counterclockwise," "axial," "radial," and "circumferential" indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are used only for the convenience of describing this invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on this invention.

[0019] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this invention, "a plurality of" means at least two, such as two, three, etc., unless otherwise explicitly specified.

[0020] In this invention, unless otherwise explicitly specified and limited, the terms "installation," "connection," "linking," and "fixing," etc., should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral part; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; they can refer to the internal communication of two components or the interaction between two components, unless otherwise explicitly limited. Those skilled in the art can understand the specific meaning of the above terms in this invention according to the specific circumstances.

[0021] In this invention, unless otherwise explicitly specified and limited, "above" or "below" the second feature can mean that the first feature is in direct contact with the second feature, or that the first feature is in indirect contact with the second feature through an intermediate medium. Furthermore, "above," "over," and "on top" of the second feature can mean that the first feature is directly above or diagonally above the second feature, or simply that the first feature is at a higher horizontal level than the second feature. "Below," "below," and "under" the second feature can mean that the first feature is directly below or diagonally below the second feature, or simply that the first feature is at a lower horizontal level than the second feature.

[0022] It should be noted that when an element is referred to as being "fixed to" or "set on" another element, it can be directly on the other element or there may be an intervening element. When an element is considered to be "connected to" another element, it can be directly connected to the other element or there may be an intervening element. The terms "vertical," "horizontal," "upper," "lower," "left," "right," and similar expressions used herein are for illustrative purposes only and do not represent the only possible implementation.

[0023] Please see Figure 1 The silicon nitride thin film testing method in one embodiment of the present invention includes the following steps S10 to S40. Wherein: Step S10: Perform initial performance testing on the sample to be tested to obtain the initial electrical performance parameters, initial passivation parameters, and initial compactness parameters of the sample to be tested.

[0024] The test sample includes the target material, namely a silicon nitride thin film. Specifically, the test sample is a TOPCon battery (tunneling oxide passivated contact battery). The surface of the TOPCon battery is covered with a silicon nitride thin film, which serves as a passivation / antireflection functional layer. Its quality directly affects the battery's conversion efficiency and long-term service reliability.

[0025] Preferably, the TOPCon battery adopts a wavy harpoon electrode structure, meaning that the harpoon-shaped junction between the fine grid electrode and the main grid electrode is wavy rather than a traditional straight line. This wavy harpoon structure alleviates stress concentration on the grid lines and blocks the linear penetration path of moisture into the silicon nitride film along the harpoon, thereby significantly reducing the probability of electrode corrosion, film peeling, and PID (potential-induced degradation) failures during subsequent high-pressure accelerated damp heat aging. More specifically, the wavy harpoon shape is a sine wave or a quasi-sine smooth curve with an amplitude of 0.03mm–0.15mm, a period of 0.2mm–1.0mm, a linewidth consistent with the fine grid electrode (30μm–60μm), and a wavy segment length of 0.5mm–3.0mm.

[0026] In one embodiment, before performing initial performance testing on the sample to be tested, a step of screening and pretreatment of the sample to be tested is also included.

[0027] The screening steps described above are as follows: Ellipsometry is used to test the film thickness, refractive index, and uniformity of the silicon nitride thin film, while EL / PL imaging equipment is used to record the initial luminescence uniformity of the sample. Samples with a film thickness deviation ≤ ±2nm, a refractive index within the range of 1.9 to 2.1, and satisfactory luminescence uniformity (i.e., no microcracks, broken grids, pinholes, peeling, or other coating defects) are selected as test samples, while samples that do not meet the requirements are discarded.

[0028] The above pretreatment steps are as follows: remove burrs from the sample edges, clean the sample surface with deionized water, and then place the sample in an oven at 60℃~80℃ for 30 minutes to eliminate internal stress and surface adsorbed water, so as to ensure the stability and repeatability of subsequent test results.

[0029] Specifically, the initial electrical performance parameters include initial series resistance, initial parallel resistance, initial conversion efficiency, and initial leakage current; the initial passivation parameters include initial minority carrier lifetime; and the initial compactness parameters include initial film thickness. The specific implementation method for the initial performance test in step S10 above is generally as follows: A photovoltaic cell tester was used to test the sample to obtain the initial series resistance Rs0, initial parallel resistance Rsh0, initial conversion efficiency Eff0, and initial leakage current Ileak0. The series resistance reflects the total contact resistance and bulk resistance between the layers within the cell, and its magnitude directly affects the fill factor. The parallel resistance reflects the leakage path within the cell; a decrease in its value indicates the presence of a local short circuit or defect. The conversion efficiency, the ratio of the cell's output power to the incident light power, is a core comprehensive indicator for evaluating cell performance. The leakage current reflects the degree of leakage under reverse bias and is an important parameter characterizing the cell's electrical integrity.

[0030] The minority carrier lifetime tester was used to test the sample to obtain the initial minority carrier lifetime τ0. Minority carrier lifetime refers to the average existence time of non-equilibrium minority carriers in a semiconductor from generation to recombination. It is a core indicator for evaluating the passivation effect of silicon nitride thin film surface. A higher minority carrier lifetime indicates a lower surface recombination rate and a better passivation effect.

[0031] The initial film thickness d0 of the silicon nitride thin film of the sample under test can be measured and recorded using an ellipsometry, and used as a benchmark reference value for subsequent compactness evaluation.

[0032] Step S20: Perform high-pressure accelerated damp heat aging treatment on the sample to be tested.

[0033] This step aims to simulate the aging process of photovoltaic cells under actual service environments such as high temperature, high humidity, and high pressure, so as to fully expose potential defects in the film layer and interface under accelerated stress. In this embodiment, the high-pressure accelerated damp heat aging treatment adopts the B-HAST (biased high accelerated stress test) mode. More specifically, the steps for high-pressure accelerated damp heat aging treatment of the sample to be tested include: setting the test parameters to a temperature of 130°C, a relative humidity of 85%RH, and a pressure of 2230kPa; then placing the sample to be tested in a test chamber for continuous testing for 96 hours, and applying a bias voltage of 0.6 to 0.8 times the open circuit voltage; and then removing the sample to be tested and placing it in an environment with a temperature of 25°C and a relative humidity of 60%RH for 4 hours to recover.

[0034] The sample to be tested was placed in the HAST test chamber, and the test environment parameters were set as follows: temperature 130℃, relative humidity 85%RH, and pressure 230kPa (approximately 2.3atm), with a test duration of 96 hours. Simultaneously, a bias voltage of 0.6–0.8 times the open-circuit voltage (i.e., 0.6Voc–0.8Voc) was applied to simulate the electric field environment of the battery under actual operating conditions, accelerating the electrochemical corrosion and PID effect. During the test, the leakage current and insulation resistance of the sample were monitored in real time. If any abnormalities such as a sudden increase in leakage current or a sudden decrease in insulation resistance occurred, the abnormal data was immediately recorded and the corresponding sample was marked. After the test, the sample was removed from the HAST test chamber and placed under standard environmental conditions of 25℃ and 60%RH for 4 hours to allow the internal temperature and humidity of the sample to stabilize, avoiding secondary damage to the silicon nitride film or electrode detachment due to rapid heating and cooling, and ensuring the accuracy of subsequent test results.

[0035] Furthermore, compared to the traditional damp heat test (DH) of 85℃ / 85%RH / 1000h, this solution employs HAST (High Accelerated Stress Test), which offers significant advantages in testing efficiency. Traditional DH testing requires 1000 hours (approximately 42 days), a testing cycle that is too long to meet the timeliness requirements of rapid verification during product development and quality control in mass production. This solution, however, raises the testing conditions to 130℃, 85%RH, and 230kPa (approximately 2.3atm). By significantly increasing temperature, humidity, and pressure, it significantly enhances the driving force for moisture penetration into the film and interface, greatly accelerating the aging process under high temperature and high pressure. Simultaneously, a bias voltage of 0.6–0.8 times the open-circuit voltage (i.e., 0.6Voc–0.8Voc) is applied during the test to simulate the electric field environment of the battery under actual operating conditions, accelerating the electrochemical corrosion and PID (potential-induced degradation) effects. By combining the synergistic effects of the above stress conditions, this solution only requires 96 hours of continuous testing to achieve the same aging effect as the conventional DH test of 1000 hours, with an acceleration ratio of approximately 10:1. The testing cycle is shortened from several weeks in the traditional solution to four days, which greatly improves the testing efficiency and can fully adapt to the rapid screening needs in the R&D stage and the quality control rhythm in the mass production stage.

[0036] Step S30: Perform another performance test on the sample after aging treatment to obtain the aging electrical performance parameters, aging passivation parameters and aging densification parameters of the sample.

[0037] This step generally uses the same or equivalent testing equipment and conditions as step S10 above to retest the samples after high-pressure accelerated damp heat aging treatment to obtain performance parameters in various dimensions after aging. Correspondingly, the aging electrical performance parameters include the series resistance, parallel resistance, conversion efficiency, and leakage current after aging; the aging passivation parameters include the minority carrier lifetime after aging; and the aging compaction parameters include the film thickness after aging.

[0038] Specifically, a photovoltaic cell tester identical to that used in step S10 above can be used to retest the series resistance Rs1, parallel resistance Rsh1, conversion efficiency Eff1, and leakage current Ileak1 of the aged sample. A minority carrier lifetime tester identical to that used in step S10 above can also be used to retest the minority carrier lifetime τ1 of the aged sample.

[0039] The density of silicon nitride thin films is the structural basis for their resistance to moisture erosion and their ability to block the migration of metal ions. The denser the film, the fewer its micropores and loose defects, and the stronger its barrier to external corrosive media. Traditional methods for assessing density, such as vacuum leak detection and immersion testing, have drawbacks such as low sensitivity, easy damage to the film layer, and inability to achieve quantitative evaluation. Therefore, in this embodiment, the aging density parameters are obtained by using hydrofluoric acid (HF) etching combined with ellipsometry thickness measurement.

[0040] Specifically, a 1% dilute hydrofluoric acid solution is prepared, and the sample to be tested is immersed in the solution for 30 seconds. After removal, it is rinsed with deionized water and dried with nitrogen. The surface morphology of the film layer of the sample is observed using an optical microscope to conduct a preliminary density test. The thickness of the sample is measured for those that pass the preliminary density test. The surface morphology of the film layer of the sample can be observed using an optical microscope (magnification of 500×), and the absence of pinholes, spots, and local peeling is used as the standard for preliminary density acceptance. For samples that pass the preliminary density test, the film thickness d1 after etching is re-measured using an ellipsometry as the aging density parameter, i.e., the film thickness after aging.

[0041] Hydrofluoric acid can react chemically with silicon nitride. When there are loose areas or micropores in the film, the etchant can penetrate more easily and expand the corrosion range, thus showing differences in film thickness loss and surface morphology. Conversely, dense films have good resistance to etchants.

[0042] Leakage current can evaluate the ability of silicon nitride thin films to block metal ion migration and resist electrochemical corrosion under the action of an electric field. In one embodiment, the step of performing a second performance test on the test sample to obtain the leakage current after aging in step S30 above includes: placing the aged test sample in a humid and hot environment with a temperature of 85°C and a relative humidity of 85%RH and applying a DC bias voltage of 10V; continuously testing for 24 hours and obtaining the leakage current after aging.

[0043] During the actual service process of a photovoltaic cell, its silicon nitride thin film not only needs to withstand the erosion of high-temperature and high-humidity environments, but is also under the long-term action of the electric field generated by the operating voltage of the module. Under these conditions, sodium ions (Na + ) and other movable metal ions may penetrate the silicon nitride thin film and migrate to the inside of the cell under the drive of the electric field, forming leakage channels. Meanwhile, the synergistic effect of water vapor and bias voltage will also cause electrochemical corrosion, leading to failure phenomena such as grid line corrosion and PID (Potential Induced Degradation). Conventional tests usually only evaluate the tolerance of thin films in a single damp-heat environment, without introducing bias voltage conditions, and cannot truly reflect the electrochemical corrosion resistance of cells under working conditions.

[0044] In addition, the above step S30 preferably further includes some auxiliary detection means to further enrich the evaluation dimensions. For example, in one embodiment, when the performance test of the sample to be tested is performed again in the above step S30, an EL / PL imaging device is also used to detect the structural defects of the sample to be tested after aging treatment, and the area proportion of the structural defects is obtained. The EL / PL imaging device is used to detect the aged sample to be tested, mainly to observe whether the sample has defects such as local blackening, dark lines, grid line corrosion, PID degradation, and film peeling, and to count the ratio of the defect area to the total area of the whole cell. This area ratio can intuitively reflect the degradation degree of the passivation quality.

[0045] In addition, the four-probe method can also be used to test the contact resistance of the grid line-silicon interface, and the initial contact resistance is compared to judge the deterioration degree of the interface before and after aging.

[0046] Step S40: The attenuation index is obtained by comparing the aged electrical performance parameters, aged passivation parameters and aged compactness parameters with the initial electrical performance parameters, initial passivation parameters and initial compactness parameters respectively, and the sample to be tested is determined to be qualified when all the attenuation indices are lower than the corresponding threshold values.

[0047] Correspondingly, the above attenuation indices include film thickness loss rate, minority carrier lifetime degradation rate, series resistance increase rate, shunt resistance degradation rate, conversion efficiency degradation rate, and leakage current increase rate. The sample to be tested is determined to be qualified when the following conditions are met: film thickness loss rate ≤ 3%, minority carrier lifetime degradation rate ≤ 25%, series resistance increase rate ≤ 15%, shunt resistance degradation rate ≤ 20%, conversion efficiency degradation rate ≤ 5%, and leakage current increase rate ≤ 200%. Only when all the above quantitative indicators simultaneously meet the corresponding threshold requirements, can the silicon nitride thin film of the sample to be tested be judged to have qualified reliability.

[0048] The film thickness loss rate is used to characterize the degree of density retention of the silicon nitride film after aging and HF etching, and is calculated by the following formula: Film thickness loss rate = (d0 - d1) / d0 × 100%; the smaller the value, the denser the film structure and the stronger its resistance to moisture and chemical corrosion. In this embodiment, a film thickness loss rate ≤3% is considered acceptable.

[0049] Minority carrier lifetime decay rate is used to characterize the degree of degradation of the passivation effect of silicon nitride thin film after aging, and is calculated by the following formula: Minority carrier lifetime decay rate Δτ = (τ0 - τ1) / τ0 × 100%; the smaller this value, the better the passivation layer can still effectively inhibit surface recombination and maintain good passivation quality after damp heat aging. In this embodiment, a minority carrier lifetime decay rate ≤25% is considered acceptable.

[0050] The increase in series resistance is used to characterize the internal contact state of the battery and the degree of degradation of the film interface after aging. It is calculated by the following formula: Series resistance increase ΔRs = (Rs1 - Rs0) / Rs0 × 100%; the smaller this value, the better the electrode contact and film interface remain after aging, and the less obvious the interface degradation or corrosion. In this embodiment, a series resistance increase ≤15% is considered acceptable.

[0051] The parallel resistance decay rate, used to characterize the increase in leakage current paths within the battery after aging, is calculated using the following formula: Parallel resistance decay rate ΔRsh = (Rsh0 - Rsh1) / Rsh0 × 100%. A smaller value indicates that the battery can still effectively suppress leakage current after aging, without significant local short circuits or defect propagation. In this embodiment, a parallel resistance decay rate ≤ 20% is considered acceptable.

[0052] The conversion efficiency degradation rate is used to comprehensively characterize the degree of performance decline of the battery after aging, and is calculated by the following formula: Conversion efficiency degradation rate ΔEff = (Eff0 - Eff1) / Eff0 × 100%; the smaller this value, the higher the output performance of the battery after undergoing rigorous aging tests. In this embodiment, a conversion efficiency degradation rate ≤ 5% is considered acceptable.

[0053] The leakage current increase is used to characterize the degree of electrical integrity degradation of the battery after aging, and is calculated by the following formula: Leakage current increase ΔIleak = (Ileak1 - Ileak0) / Ileak0 × 100%; the smaller this value, the better the battery can maintain good insulation performance after aging. In this embodiment, a leakage current increase ≤200% is considered acceptable.

[0054] It should be noted that the auxiliary qualitative indicators obtained in step S30 above must also meet the following requirements: the defect area ratio in EL / PL imaging detection is ≤1%, and there is no significant increase in the gate-silicon interface contact resistance. That is, only when the area ratio is ≤1%, the minority carrier lifetime decay rate is ≤25%, and there is no significant increase in the gate-silicon interface contact resistance can it be said that the passivation quality meets the requirements.

[0055] In one embodiment, in step S30 above, after the sample to be tested is tested again, a step of high temperature thermal stability testing is also included: the aged sample to be tested is placed in a vacuum oven at 200°C and kept at that temperature for 1 hour, and then naturally cooled to room temperature; the minority carrier lifetime and conversion efficiency after high temperature treatment are retested, and the high temperature performance degradation rate is obtained. Only when the high temperature performance degradation rate is ≤2% can the sample to be tested be determined as qualified.

[0056] This step is primarily for high-temperature thermal stability testing to evaluate the performance retention capability of silicon nitride thin films under high-temperature environments. The performance degradation rate after high-temperature treatment (including minority carrier lifetime degradation and conversion efficiency degradation) must be ≤2%. If any of the above indicators fails to meet the corresponding threshold requirements, the silicon nitride thin film of the test sample is deemed unreliable.

[0057] In addition, in one embodiment, before performing a second performance test on the aged sample, the method further includes the step of performing a microscopic morphology analysis on the sample by scanning electron microscopy-energy dispersive spectroscopy, and determining the sample that fails the morphology analysis as unqualified.

[0058] Specifically, SEM-EDS (Scanning Electron Microscopy-Energy Dispersive Spectroscopy) is used to observe the microstructure of the sample, focusing on the surface morphology and cross-sectional structure of the silicon nitride film, as well as the interface state between the wavy-lined harpoon electrode and the film. This is done to detect failure phenomena such as grid line corrosion, film cracks, interface delamination, and impurity enrichment, in order to pinpoint the root cause of the failure. If any of these failure phenomena are found in the morphology analysis, the sample is directly deemed unqualified, and no further quantitative comparison is required. Quantitative comparison will only proceed if the wavy-lined harpoon electrode shows no obvious corrosion, and the interface between the silicon nitride film and the electrode shows no delamination or obvious water vapor penetration traces.

[0059] The aforementioned silicon nitride thin film testing method effectively simulates the aging process of the sample under test, such as a photovoltaic cell, in actual service environments with high temperature, high humidity, and high pressure through high-pressure accelerated damp-heat aging treatment. This fully exposes potential defects in the film layer and interface under accelerated stress, avoiding the evaluation distortion caused by conventional testing due to unrealistic operating conditions. Simultaneously, by acquiring and comparing the electrical performance parameters, passivation parameters, and density parameters before and after aging treatment, a comprehensive quantitative evaluation of the silicon nitride thin film across multiple dimensions is achieved, effectively avoiding incomplete information or misjudgments caused by testing a single indicator. Therefore, the accuracy of the aforementioned silicon nitride thin film testing method is greatly improved, and its test results can truly reflect the film quality and the overall reliability of the photovoltaic cell.

[0060] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0061] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.

Claims

1. A method for testing silicon nitride thin films, characterized in that, Including the following steps: Initial performance tests are performed on the sample to be tested to obtain the initial electrical performance parameters, initial passivation parameters, and initial compactness parameters of the sample to be tested. The sample to be tested was subjected to high-pressure accelerated damp heat aging treatment; The test sample after aging treatment is subjected to another performance test to obtain the aging electrical performance parameters, aging passivation parameters and aging densification parameters of the test sample. The decay index is obtained by comparing the aging electrical performance parameters, the aging passivation parameters, and the aging densification parameters with the initial electrical performance parameters, the initial passivation parameters, and the initial densification parameters, respectively. The sample is deemed qualified when the decay index is lower than the corresponding threshold.

2. The silicon nitride thin film testing method according to claim 1, characterized in that, The sample to be tested is a TOPCon battery, and the surface of the TOPCon battery is covered with a silicon nitride thin film.

3. The silicon nitride thin film testing method according to claim 1, characterized in that, Before conducting initial performance testing on the sample to be tested, the method further includes the following steps: detecting the film thickness, refractive index, and luminescence uniformity of the sample, and selecting samples with film thickness deviation ≤ ±2nm, refractive index between 1.9 and 2.1, and qualified luminescence uniformity as the sample to be tested.

4. The silicon nitride thin film testing method according to claim 1, characterized in that, Before performing another performance test on the sample after aging treatment, the method further includes the following steps: performing microscopic morphology analysis on the sample by scanning electron microscopy-energy dispersive spectroscopy, and determining the sample that fails the morphology analysis as unqualified.

5. The silicon nitride thin film testing method according to claim 1, characterized in that, The steps for subjecting the test sample to high-pressure accelerated damp heat aging treatment include: setting the test parameters to a temperature of 130℃, a relative humidity of 85%RH, and a pressure of 2230kPa; then placing the test sample in a test chamber for continuous testing for 96 hours, and applying a bias voltage of 0.6 to 0.8 times the open circuit voltage; and finally removing the test sample and placing it in an environment with a temperature of 25℃ and a relative humidity of 60%RH for 4 hours to recover.

6. The silicon nitride thin film testing method according to claim 1, characterized in that, The initial electrical performance parameters include initial series resistance, initial parallel resistance, initial conversion efficiency, and initial leakage current; the initial passivation parameters include initial minority carrier lifetime; and the initial compaction parameters include initial film thickness. The aging electrical performance parameters include series resistance after aging, parallel resistance after aging, conversion efficiency after aging, and leakage current after aging; the aging passivation parameters include minority carrier lifetime after aging; and the aging compaction parameters include film thickness after aging. The degradation index includes film thickness loss rate, minority carrier lifetime decay rate, series resistance increase, parallel resistance decay rate, conversion efficiency decay rate, and leakage current increase. The sample to be tested is deemed qualified when the film thickness loss rate is ≤3%, the minority carrier lifetime decay rate is ≤25%, the series resistance increase is ≤15%, the parallel resistance decay rate is ≤20%, the conversion efficiency decay rate is ≤5%, and the leakage current increase is ≤200%.

7. The silicon nitride thin film testing method according to claim 6, characterized in that, When performing a second performance test on the sample to be tested, an EL / PL imaging device is also used to detect the structural defects of the sample after aging treatment, and the area ratio of the structural defects is obtained. Only when the area ratio is ≤1% can the sample be judged as qualified.

8. The silicon nitride thin film testing method according to claim 6, characterized in that, The step of performing a second performance test on the sample to be tested to obtain the film thickness after aging includes: Prepare a 1% dilute hydrofluoric acid solution, immerse the sample to be tested in the solution for 30 seconds, remove it, rinse it with deionized water and then dry it with nitrogen gas; observe the surface morphology of the film layer of the sample to be tested using an optical microscope to conduct a preliminary test of its density; measure the thickness of the sample to be tested if the preliminary test of density is qualified.

9. The silicon nitride thin film testing method according to claim 6, characterized in that, The steps for performing a second performance test on the test sample to obtain the leakage current after aging include: placing the aged test sample in a humid and hot environment with a temperature of 85°C and a relative humidity of 85%RH and applying a DC bias voltage of 10V; continuously testing for 24 hours and obtaining the leakage current after aging.

10. The silicon nitride thin film testing method according to claim 1, characterized in that, After the sample to be tested is tested again, the high temperature thermal stability test is also included: the aged sample to be tested is placed in a vacuum oven at 200°C for 1 hour and then naturally cooled to room temperature; the minority carrier lifetime and conversion efficiency after high temperature treatment are retested and the high temperature performance degradation rate is obtained. The sample to be tested can be judged as qualified only when the high temperature performance degradation rate is ≤2%.